DAMPAK PENGGUNAAN GADGET TERHADAP MOTIVASI BELAJAR SISWA DAN SISWI SMAN 34 JAKARTA - Najmah Dhiyaa Ulhaq; Muhammad Fauzan Rhadiansyah, Naura Ad’hani, Muhammad Zaidan Triandra Putra, Maulana Ibrahim, Kirana (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to examine the impact of gadget usage on the learning motivation of students at SMAN 34 Jakarta. The research was conducted at SMAN 34 Jakarta. The subjects of this research are the students of SMAN 34 Jakarta. The research used a quantitative approach. The data collection technique in this study was a questionnaire survey. The results indicate that the majority of students stated that the use of gadgets can increase learning motivation, facilitate access to information, make learning activities more engaging, and enhance creativity. Based on the questionnaire data, 73.8% of students stated that gadgets improve learning motivation, and 72.3% stated that gadgets are useful as a medium for finding assignments, news, and information. Meanwhile, 66.2% of students stated that gadgets make it difficult for them to concentrate while studying, 20% stated that gadgets reduce their interest in learning, and 13.8% felt that gadgets make them more individualistic. To minimize the negative impacts of gadgets, it is necessary to use them wisely to provide significant benefits in supporting learning activities.